Análise acústica dos formantes em indivíduos com deficiência isolada do hormônio do crescimento - Valença, Eugênia Hermínia Oliveira (2014)
Voice is produced by vibration of the vocal folds, whose number of cycles per second corresponds to the fundamental frequency (f0) of the laryngeal signal. Formants (F) are multipleof (f0), indicatingtheresonance frequency of the vowels in the vocal tract. The first formant (F1), relates to sound amplification in posterior oral cavity and vertical position of the tongue; and the second formant (F2) relates to the anterior oral cavity and to the horizontal position of the tongue. The third formant (F3) is related to the position front and behind of the apex of the tongue, the fourth formant (F4) relates to the shapeof larynx and pharynx at the same height. We identified a cohort of individuals with isolated growth hormone (GH) deficiency (IGHD) caused by the homozygous c.57 +1 G> A mutation in the GH releasing hormone receptor gene, with severe short stature, accentuated reduction of maxillaries, and laryngeal constriction. The voice of IGHD individuals presents high f0, regardless of age and gender. Our objective was to analyze F1, F2, F3 and F4 of the seven oral vowels in Brazilian Portuguese, [a, ε, e, i, o, u]. A cross-sectional study was conducted with 33IGHD individuals, 44.48 (17.60) years, 16 women, and 29 controls, 51.10 (17.65) years, 15 women by a computed acoustics analyze. In addition, it was analyzed a subgroup of 13 men (5 with IGHD) and 20 women (9 IGHD), above 50 years of age. Values were expressed as mean (standard deviation) or median (interquartile range). The comparison between groups was made by Student s t and Mann-Whitney tests and of the vowel in the same formant, by the paired t test. Compared to controls, IGHD men show higher values of F3 [i, e and ε], p=0.006, p=0.022 and, p=0.006, respectively, and F4[i], p=0.001 and lower values of F2 [u] p=0.034. IGHD women, higher values of F1[i and e] p=0.029 and p=0.036; and F2[ ] p = 0.006; F4[ ], p= 0.031; and lower values of F2[i] p=0.004. Men and women IGHD have similar values of formant frequencies, except for F1 [a, ó and ε] p< 0.0001, p=0.004 and p= 0.001, respectively. Men and women IGHD did not present distinction in the pair vowel high and medium high in F1 [u-o]. In both groups were observed the distinction in F2 vowel anterior-posterior. Over 50 years of age, IGHD men have lower values of F1 [i, o] p=0.042, p=0.040; and IGHD women, higher values of F1 [ε] p=0.018. In conclusion, IGHD subjects exhibit higher values of formants frequencies, suggesting shortening of vocal tract. IGHD reduces the effect of aging and gender on the formant structure.